2016
DOI: 10.1039/c6sm01257d
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of the magnetic properties of soft magnetic gels

Abstract: We present results of an experimental and theoretical study of the magnetic properties of soft magnetic gels consisting of micron-sized magnetizable particles embedded in a polymer matrix. Experiments demonstrate hysteretic dependences of composite magnetization on an applied magnetic field and non-monotonic, with maximum, dependence of the sample susceptibilities on the field. We propose a theoretical approach which describes the main physical features of these experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…Similar hysteresis is observed also for field-induced modifications of rheological and other properties of soft MAEs. 40,[44][45][46] From the obtained values of (B), an estimation of surface roughness can be made by considering a suitable model of surface topography. For this purpose, lateral dimensions of topographical features deduced from optical microscopy images can be taken into account.…”
Section: Field-induced Modifications Of Surface Topographymentioning
confidence: 99%
“…Similar hysteresis is observed also for field-induced modifications of rheological and other properties of soft MAEs. 40,[44][45][46] From the obtained values of (B), an estimation of surface roughness can be made by considering a suitable model of surface topography. For this purpose, lateral dimensions of topographical features deduced from optical microscopy images can be taken into account.…”
Section: Field-induced Modifications Of Surface Topographymentioning
confidence: 99%
“…For maximal simplification of the mathematical part of the problem, we will suppose that the particles are identical. Like in [ 54 , 55 ], we will neglect fluctuations of the chain’s shape and will consider them as ideally straight aggregates, aligned along the applied magnetic field H . This model of the chain is illustrated in Figure 1 .…”
Section: Physical and Mathematical Modelmentioning
confidence: 99%
“…Strictly speaking, the value of a particle moment depends on the number i of the particle position in the chain. However, analysis [ 55 ] shows that approximation, where magnetic moments of all of the particles in the chain are supposed identical, leads to not significant deviations from the strict approach. That is why we will use the simplest approximation of identity of the particle moments in the chain.…”
Section: Physical and Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They also calculated the normal stress with different initial configurations and found that the particle structure had a big influence on the squeeze flow behavior. The influence of the particle structure on the performance of MR materials has been widely researched [23][24][25], and the results show that destroying the particle structure decreases the normal stress.…”
Section: Introductionmentioning
confidence: 99%